Kesedaran penjimatan tenaga elektrik mengikut perbezaan latar belakang pengguna - Shaharuddin, Ismail (2017)
Awareness on saving electricity in Perlis is still at an inadequate level nowadays. This study argues that the user's background influences in determining awareness on saving electricity among Perlis users. The objectives of this study are: first, determining the level of consumer awareness on saving electricity; second, identifying the difference between the user background and the awareness of saving electricity; and third, examining relations between user’s background and consumer awareness on saving electricity. This study involved 384 respondents from three areas in Perlis namely the main city (Kangar), other cities (namely Arau, Kuala Perlis, Padang Besar and Simpang Empat) and rural areas. Data analysis is based on the objective of the study involving descriptive techniques, one way ANOVA and regression. The findings of the first objective show that the mean level of awareness on saving electricity is 2.71, which can be considered higher than previous studies. The analysis on differences for the second objective shows that the constructs of the residential area and educational status of the respondents determine the difference in saving electricity awareness. Meanwhile, the analysis of the third objective found that the overall background of consumers determined the awareness on saving energy among consumers in Perlis. Therefore, the study suggests that a form of coordination of awareness activities should be carried out by the authorities such as Tenaga Nasional Berhad, the ministries, local authorities or local representatives throughout the state of Perlis towards minimizing the differences in consumer awareness on saving electricity due to area of living